Efeitos do apagamento da exceção na contemporaneidade - Michelle Santos Sena de Oliveira (2017)
The present study aims to elucidate the paths and effects of the erasing of exception on contemporaneity through a psychoanalytical perspective. Based on the acknowledgment of the predominance of evaluation practices that influence many areas on contemporaneous life, we engage on the investigation of the secularization of the world that impacts on the current social bond formation, that is not substantiated on an exception. The politics regime of Antiquity was based on an exception that was not subjected to the laws prescribed by itself. The erasing of this exception function occurs in modernity, caused by the development of modern science and capitalism. A new discourse organization is proposed and it is guided by the knowledge of the utilitarian scientist. From the ancient master’s discourse to the modern master’s discourse, academic and capitalist, the knowledge obtained by the measure of the utility and of the value starts orienting political and individual decisions, previously guided by tradition. Before this reality, the bureaucratic administration directs toward the subjects, striving to homogenize and subordinate them to the modern ideal of transparency, guaranteed by the knowledge extracted and decoded by the evaluation apparatus. The realm of norm and contract supersedes the ancient realm of law. In the modern world, there is no activity nor subject that is not submitted to the behest of the all-knowing. Psychoanalysis gathers the effects from this contemporary social bond, nonetheless, in a distinct form from the dominant discourse, offers another destiny to intimacy, to the opaque of the sinthome and to that of jouissance that can not be accounted for, neither homogenized.